Collaborative Governance in Natural Disaster Mitigation in Bekasi Regency, Indonesia - Khaerul Umam Noer; Sipin Putra (Universitas Sebelas Maret, 2022)
This article examines the role of collaborative governance in natural disaster mitigation in Bekasi Regency, focusing on three sectors: the Regional Disaster Management Agency, the village government apparatus, and the community. This study will examine each party's involvement in mitigating natural disasters in particular. This study discovered a significant number of key findings by employing an ethnographic method and analysis with the Ansel and Gash model. First, there is an imbalance between stakeholders, with the community lacking in disaster mitigation training and awareness. Second, in terms of facilitative leadership, the role of district government and community leaders as mediators is not yet broad enough to promote collaborative events in disaster management, and the community is unaware of its involvement in this collaborative endeavor. Third, on the institutional level, there is no memorandum of understanding amongst the stakeholders involved that describes this collaborative program in further detail. Furthermore, there is little transparency in the program because the community has been excluded a wide range of opportunities to participate. Fourth, there are five indications in the collaborative process as a core dimension in collaborative governance: face-to-face interaction, trust between stakeholders, forging common commitments, harmonizing perspectives, and preliminary results of collaborative effort. In this situation, the forum is not organized on a regular basis, but just at particular times, resulting in less successful and ideal collaborative disaster management outcomes.